INTERNET-BASED APPROACH IN DISTANCE LEARNING OF PARAGRAPH-WRITING COURSE AT STKIP MUHAMMADIYAH BARRU - Siti Hardiyanti Amri (JOALL (Journal of Applied Linguistics and Literature), 2020)
The era of COVID-19 transforms the traditional classroom into the fully online distance learning system. This new learning mode presents new challenges to both the lecturer and students at the College of Teacher Training and Education (STKIP) Muhammadiyah Barru, Indonesia. This research focused on identifying the types of online platforms applied in distance learning of paragraph writing course, the students’ behaviors and challenges toward the learning system, and the English skill output of the learning process. The method was qualitative descriptive consisting of data collection and data analysis. The data was gathered by interviewing and observing the participants. The data was then analyzed by using distance learning concepts of Cynthia White. The result indicated that the class made use of Multi-synchronous distance learning. However, they preferred to make use the asynchronous distance learning due to the flexibility of time and space, also its cost-effective. Besides, the research found that the students fast adapted to the new learning context for the ability to operate technology, yet they did not fully understand their roles and responsibilities during the learning process. Moreover, as the challenges of self-independent demand, self-awareness and management and the slow internet access of their isolated areas, most of the students did not show satisfied output in writing English paragraph.